Controversial animal tourism considered from a cultural perspective - Malchrowicz-Mośko, Ewa; Munsters, Wil; Korzeniewska-Nowakowska, Paulina; Gravelle, François (Turyzm/Tourism, 2020)
An aspect of controversial animal tourism that has received little attention is its relationship with cultural tourism. The article presents a categorization of cultural tourism, and sports attractions and events related to the abuse of animals. It shows how tourists, driven by cultural omnivorousness and the wish to stand out from the crowd, eagerly enjoy controversial forms of animal tourism on their travel. In order to avoid the pitfall of western ethnocentrism ending in accusations of barbarism, the issue is also reflected on from an intercultural point of view, which helps to understand that local communities have different attitudes to animals and their wellbeing. In addition, a historical overview shows that ‘animal friendliness’ does not have a long tradition in western thinking about the human-animal relationship and is only of recent date. Sustainable solutions for controversial animal tourism have to be found by raising tourists’ awareness by means of information and education.